2014
DOI: 10.1182/blood-2013-07-517151
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of cellular deficiency in GATA2 mutation

Abstract: • Diverse patient groups with GATA2 mutation develop mononuclear cytopenia and elevated Flt3 ligand. • Progressive cytopenias, risingFlt3 ligand, and terminal differentiation of lymphoid cells accompany clinical progression.Constitutive heterozygous GATA2 mutation is associated with deafness, lymphedema, mononuclear cytopenias, infection, myelodysplasia (MDS), and acute myeloid leukemia. In this study, we describe a cross-sectional analysis of 24 patients and 6 relatives with 14 different frameshift or substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
277
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(290 citation statements)
references
References 55 publications
9
277
0
4
Order By: Relevance
“…This could be due to a converted HSC signature or more likely to the loss of the Gata2-deficient HSCs in line with observations in haploinsufficient Gata2 mice 19 and with Gata2-deficient human BM showing a complete absence of the primitive CD38 -cells within the CD34 + progenitor compartment [43][44][45] . Even though we were limited to study progenitor-enriched Gata2-deficient cells we found these cells to exhibit a strong reduction of colony-forming ability and to be desensitized to TGFβ-induced growth arrest.…”
Section: Discussionsupporting
confidence: 78%
“…This could be due to a converted HSC signature or more likely to the loss of the Gata2-deficient HSCs in line with observations in haploinsufficient Gata2 mice 19 and with Gata2-deficient human BM showing a complete absence of the primitive CD38 -cells within the CD34 + progenitor compartment [43][44][45] . Even though we were limited to study progenitor-enriched Gata2-deficient cells we found these cells to exhibit a strong reduction of colony-forming ability and to be desensitized to TGFβ-induced growth arrest.…”
Section: Discussionsupporting
confidence: 78%
“…on May 9, 2018. by guest www.bloodjournal.org From deficiency) may cause bone marrow failure and are not widely taken into consideration, these entities need to be mentioned here (Figure 1, lower right quadrant; Table 1). 3,[72][73][74] In contrast to the widespread view of a PID diagnosis being dependent on compromised immunity, patients with GATA2 deficiency, as with other PID-linked cytopenias, may be asymptomatic and may lack a history of severe infections. 74 Because of its presentation as SCID with granulocytopenia or pancytopenia and deafness, reticular dysgenesis (deficiency of AK2) is unlikely to be missed during a differential diagnosis.…”
Section: Bone Marrow Failure In Pidmentioning
confidence: 99%
“…3,[72][73][74] In contrast to the widespread view of a PID diagnosis being dependent on compromised immunity, patients with GATA2 deficiency, as with other PID-linked cytopenias, may be asymptomatic and may lack a history of severe infections. 74 Because of its presentation as SCID with granulocytopenia or pancytopenia and deafness, reticular dysgenesis (deficiency of AK2) is unlikely to be missed during a differential diagnosis. The deficiency of IKAROS, a zinc finger transcription factor essential during hematopoiesis, 75 has been reported to be associated with hematologic malignancies (reviewed in Wang et al 76 ) and also with congenital pancytopenia in humans.…”
Section: Bone Marrow Failure In Pidmentioning
confidence: 99%
“…10,12 MDS manifests in GATA-2-deficient patients earlier than in the general population. 11 A GATA2 mutation in pediatric non-familial MDS patients was found in 16% of patients with aberrant karyotype (monosomy 7). 13 Flow cytometry is recognized to be an important diagnostic method especially in adult forms of MDS.…”
Section: Loss Of B Cells and Their Precursors Is The Most Constant Fementioning
confidence: 99%
“…5 A mutation in the GATA2 gene, which encodes the transcription factor GATA-2, was recently found by whole genome sequencing 6,7 or by candidate approaches 8,9 as a common cause of several overlapping syndromes: familial MDS/acute myeloid leukemia (AML), dendritic cell, monocyte, B-and NK-lymphoid (DCML) deficiency, mycobacterial infections and monocytopenia (MonoMAC), and hereditary lymphedema (Emberger syndrome). 6,7 Several abnormalities, identifiable by flow cytometry (FC) in peripheral blood (PB), are known to be present in patients with GATA2 mutations: a decreased number of B cells, NK cells, monocytes and dendritic cells; 10,11 plasma cells with an aberrant immunophenotype in bone marrow (BM); clonal T-large granular lymphocyte (LGL) proliferation; and aberrant maturation patterns of granulocytic lineage. 10,12 MDS manifests in GATA-2-deficient patients earlier than in the general population.…”
Section: Loss Of B Cells and Their Precursors Is The Most Constant Fementioning
confidence: 99%